Planning Linkages between Research, Technology Transfer, and Farmers' Organizations - Eponou, Thomas; Peterson, Warren; Wuyts-Fivawo, Anna; Wilks, M. (International Service for National Agricultural Research, 1999)
Linkages between major institutional actors in agricultural knowledge and information systems (AKIS) are widely recognized as essential for an effective flow of technology and information between research, extension, and farmers. The types and nature of linkages between actors within an AKIS directly influence its effectiveness for improving levels of production, particularly for noncommercial and resource-poor producers. It is commonly recognized by AKIS stakeholders that poor performance of the system is often related to linkage problems. The report is based on a project designed to assist four participating countries (Senegal, Mali, Tanzania, and Zimbabwe) in addressing their research-user linkage problems, in building a capacity to analyze and resolve these problems, in improving methods and guidelines for linkage planning and implementation, and in disseminating linkage knowledge, lessons, and experiences. It presents the important lessons that were learned from the experiences, and lists the identified requirements to ensure that linkage planning and implementation succeeds.